2012
DOI: 10.1016/j.drudis.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and therapeutic effects of A3 adenosine receptor agonists

Abstract: The Gi-coupled A3 adenosine receptor (A3AR) mediates anti-inflammatory, anticancer and anti-ischemic protective effects. The receptor is overexpressed in inflammatory and cancer cells, while low expression is found in normal cells, rendering the A3AR as a potential therapeutic target. Highly selective A3AR agonists have been synthesized and molecular recognition in the binding site has been characterized. The present review summarizes preclinical and clinical human studies demonstrating that A3AR agonists indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
225
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(236 citation statements)
references
References 70 publications
6
225
1
4
Order By: Relevance
“…A role of the A3R was also excluded because the receptor is insensitive to DPCPX antagonism. 17 However, even though these findings indicated an exclusive involvement of brain A1R, to our surprise we found that Ado injected intraperitoneally or i.c.v. was less hypothermic than AMP (Figures 2A and 2B).…”
Section: Pharmacological Modulation Of Adenosine 5 0 -Monophosphatedecontrasting
confidence: 53%
“…A role of the A3R was also excluded because the receptor is insensitive to DPCPX antagonism. 17 However, even though these findings indicated an exclusive involvement of brain A1R, to our surprise we found that Ado injected intraperitoneally or i.c.v. was less hypothermic than AMP (Figures 2A and 2B).…”
Section: Pharmacological Modulation Of Adenosine 5 0 -Monophosphatedecontrasting
confidence: 53%
“…MRS5698 includes multiple structural features that were optimized for potency and selectivity at the target A 3 AR, such as a [3.1.0]bicyclohexane ring system in place of ribose and a rigid extension at the C2 position. Several earlier A 3 agonists (ribosides IB-MECA (CF101), only 50-to100-fold selective in rat, and Cl-IB-MECA (CF102)) from our lab are currently in clinical trials for other indications (inflammatory diseases and cancer) [13]. MRS5698 displays higher affinity and selectivity (>3000-fold) vs. other ARs in both human and mouse, and both factors are consistent across species.…”
Section: Introductionmentioning
confidence: 94%
“…Blockade of adenosine A 2A receptor leads to inhibition of adenosinergic effects and inhibits immunosuppressive potential of T regs in tumor microenvironment [228]. Recently, it has been shown that adenosine receptor A 3 (A 3AR ) agonists have a protective action in various types of cancers (i.e., melanoma, prostate cancer, colon cancer, breast cancer, and hepatocellular carcinoma) through modulation of NF-κB and Wnt signaling pathways [229]. Adenosine A 3 receptor agonists have also inhibited the breast tumor-derived bone metastasis growth [230].…”
Section: Future Perspectivementioning
confidence: 99%